Exploitation of a Learner Corpus: Analysing Openings and Endings in Academic Forums* - Castillo Rodríguez, Cristina; Díaz Lage, José María (Opción, 2015)
The main aim of this paper is to analyse a learner corpus containing original written productions in the compulsory forums created in a concrete undergraduate subject. The reason for choosing the forum is that it is a space in which students can discuss in a more spontaneous way. The corpus compiled for this study will be managed with the corpus management software program AntConc. The study will be focused on the way these students have contributed to the forums but paying special attention to the expressions used in their openings and endings in written participations.